Eficiência do uso da radiação solar por plantas Ilex paraguariensis A. St. Hil. cultivadas sob sombreamento e a pleno sol - Braulio Otomar Caron; Denise Schmidt; Paulo Augusto Manfron; Alexandre Behling; Elder Eloy; Carlos Busanello (Ciência Florestal, 2014)
The efficiency of conversion of the solar radiation in biomass is a variable frequently used in models of simulation the culture growth, because the biomass production is related with the efficiency of which a plant converts radiant energy in chemistry, given by the process of the photosynthesis. The objective of this work was to determine the efficiency of conversion of the photosynthetically active and intercepted solar radiation (RFAi) in Ilex paraguariensis biomass, cultivated in consortium ( Ilex paraguariensis A. St. Hil. e Pinus elliottii Engelm) and single. For so much, it was determined the photosynthetically active and intercepted solar radiation (RFAi), the index of leaf area and the biomass dries of the seedlings, being then, the efficiency of conversion of RFAi in biomass dries of the cultivated in consortium and single. For a same radiation value RFAi, is obtained larger when Ilex paraguariensis is cultivated in consortium. The conversion efficiency ( ε b ) of biomass total drought of Ilex paraguariensis plants in relation to the amount of the photosynthetically active and intercepted solar radiation (RFAi) accumulated is of 0.83 g MJ -1 in the system consortium and of 0.23 g MJ -1 in the single system. In spite of that, the production of aerial biomass for plant was larger in the single system.